PAJAK TANGGUHAN: RELEVANSI NILAI DAN PENDETEKSIAN MANAJEMEN LABA - Nunung Nuryani; Yuli Surya Fauzia; Jasson Abelardo (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2022)
The rules relating to deferred tax disclosure have experienced rapid improvements, both in IFRS, US GAAP, and accounting standards in Indonesia. However, the usefulness of deferred tax accounting is still a matter of debate. Many argue that the low informative value of deferred tax is related to the uncertainty of its implications for cash flows, so that users of financial statements tend to ignore deferred tax information. Empirical evidence on the value relevance of deferred tax information is still not conclusive. However, several recent research results show that in addition to having value relevance, deferred tax information is considered to be able to detect earnings management practices. This study aims to re-examine whether deferred tax information has value relevance and can be used to detect earnings management? By using the judgment sampling method, 70 manufacturing companies were obtained during the 2010-2019 period. The results of this study indicate that deferred tax information is relevant in making investment decisions and is a significant indicator for detecting earnings management practices.